Association of adolescent lipoprotein subclass profile with carotid intima-media thickness and comparison to adults: Prospective population-based cohort studies. (January 2022) - Pechlaner, Raimund; Friedrich, Nele; Staudt, Anna; Gande, Nina; Bernar, Benoît; Stock, Katharina; Kiechl, Sophia J.; Hochmayr, Christoph; Griesmacher, Andrea; Petersmann, Astrid; Budde, Kathrin; Stuppner, Hermann; et al.
Abstract: Background and aims: Assessment of comprehensive lipoprotein subclass profiles in adolescents and their relation to vascular disease may enhance our understanding of the development of dyslipidemia in early life and inform early vascular prevention. Methods: Nuclear magnetic resonance was used to measure lipoprotein profiles, including lipids (cholesterol, free cholesterol, triglycerides, phospholipids) and apolipoproteins (apoB-100, apoA1, apoA2) of 17 lipoprotein subclasses (from least dense to densest: VLDL-1 to −6, IDL, LDL-1 to −6, HDL-1 to −4) in n = 1776 14- to 19-year olds (56.6% female) and n = 3027 25- to 85-year olds (51.5% female), all community-dwelling. Lipoprotein profiles were related to carotid intima-media thickness (cIMT) as ascertained by sonography. Results: Adolescents compared to adults had lower triglycerides, total, LDL, and non-HDL cholesterol, and apoB, and higher HDL cholesterol. They showed 26.6–59.8% lower triglyceride content of all lipoprotein subclasses and 21.9–51.4% lower VLDL lipid content. Concentrations of dense LDL-4 to LDL-6 were 36.7–40.2% lower, with also markedly lower levels of LDL-1 to LDL-3, but 24.2% higher HDL-1 ApoA1. In adolescents, only LDL-3 to LDL-5 subclasses were associated with cIMT (range of differences in cIMT for a 1-SD higher concentration, 4.8–5.9 μm). The same associations emerged in adults, with on average 97 ± 42% (mean ± SD) larger effect sizes, in addition to LDL-1 and LDL-6 (range, 6.9–11.3 μm) and HDL-2 to HDL-4, ApoA1, and ApoA2 (range, −7.0 to −17.7 μm). Conclusions: Adolescents showed a markedly different and more favorable lipoprotein profile compared to adults. Dense LDL subclasses were the only subclasses associated with cIMT in adolescents, implicating them as the potential preferred therapeutic target for primary prevention of cardiovascular disease at this age. In adults, associations with cIMT were approximately twice as large as in adolescents, and HDL-related measures were additionally associated with cIMT. Graphical abstract: Image 1 Highlights: Lipoprotein subclass profiles and their associations with intima-media thickness were compared in adolescents vs . adults. Adolescents featured lower concentrations of VLDL and LDL subclasses, but results for HDL subclasses were heterogeneous. Only denser LDL subclasses were associated with intima-media thickness in adolescents. LDL and HDL subclasses were associated with intima-media thickness in adults. Associations with intima-media thickness were approximately twice as large in adults than in adolescents.